2015
DOI: 10.1186/s12891-015-0655-6
|View full text |Cite
|
Sign up to set email alerts
|

Specific exercise training for reducing neck and shoulder pain among military helicopter pilots and crew members: a randomized controlled trial protocol

Abstract: BackgroundFlight-related neck/shoulder pain is frequent among military helicopter pilots and crew members. With a lifetime prevalence of 81 % for pilots and 84 % for crew members, the prevalence of neck pain is considered high compared to the general population. The aim of this study was to investigate whether a specifically tailored exercise intervention would reduce the prevalence and incidence rate of neck/shoulder pain among helicopter pilots and crew members.MethodThis study used a prospective, parallel g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 43 publications
(58 reference statements)
0
29
0
2
Order By: Relevance
“…The intervention period was 20-weeks with pre-intervention baseline measurements and post-intervention follow-up measurements. A detailed protocol paper has been published previously [13]. The trial was conducted within the RDAF from November 2013 to April 2014.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The intervention period was 20-weeks with pre-intervention baseline measurements and post-intervention follow-up measurements. A detailed protocol paper has been published previously [13]. The trial was conducted within the RDAF from November 2013 to April 2014.…”
Section: Methodsmentioning
confidence: 99%
“…All methods have been previously described [13], and will therefore only be explained briefly. Anthropometric measurements included: height, seated height, weight and body mass index (BMI) (Composition Analyzer Tanita Corporation of America, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors demonstrated the relation of MSD with psychosocial risks. Murray et al [202] proposed physical exercise to diminish neck and shoulder pain in helicopter pilots and crews in order to reduce ailments. Tafazzol et al [204] used the NMQ, among other methods, to study the symptoms of MSd among luggage handlers in airports.…”
Section: Othersmentioning
confidence: 99%